The dilemma of a responsible intermediary : why it is time to reassess the European intermediary liability regime - Toivonen, Janna (My University, 2019)
This thesis contextualizes the latest developments in the field of intermediary liability regulation within the European Union. Special focus is given to online platforms, such as social networks and search engines, which are increasingly enlisted to regulate and police illegal user-generated content as part of the EU Digital Single Market Strategy. To this end, Commission has not only introduced new legislation, but also – and perhaps more importantly – non-binding policies, which endorse platforms’ self-regulation and enhanced responsibilities. Tendency to increase intermediary liability has also become apparent from the recent European case law. Intermediary responsibility which constitutes the latest trend in online governance has led to a two-fold dilemma. First, it is incompatible with Articles 14 and 15 of the E-Commerce Directive, under which intermediaries have traditionally enjoyed protection against secondary liability. Second, outsourcing adjudication of fundamental rights to commercially driven platforms through self-regulation results in private enforcement which, in turn, causes a risk of collateral censorship. The key finding of this thesis is that the horizontal liability framework of the E-Commerce Directive in its current form does not provide legal certainty to the platforms nor does it recognize the distinct characteristics of different types of illegal content. When combined with contradictory hard-law and soft-law instruments that further enhance platforms’ duties of care, the rules fail to safeguard the efficient exercise of fundamental rights and freedoms online, in particular the freedom of expression. This thesis argues that the EU legislator has a positive obligation to enact a clear legal framework that vertically recognizes the features of different online infringements and ensures that the fundamental rights at stake are sufficiently balanced. Only then can the non-binding self-regulation be used as a complementary measure to ensure flexibility.
Keywords: intermediary liability, platforms, private enforcement, self-regulation, freedom of expression